Role of magnetic resonance spectroscopy to differentiate high-grade gliomas from metastases - Qun Wang; JiaShu Zhang; WeiLin Xu; XiaoLei Chen; JianMin Zhang; BaiNan Xu (Tumor Biology)
This study is to measure the diagnostic examination quality of magnetic resonance spectroscopy in differentiating high-grade gliomas from metastases. PubMed, Embase, and Chinese Biomedical databases were systematically searched for relevant studies published through 10 July 2016. Based on the data from eligible studies, heterogeneity and threshold effect tests were performed; pooled sensitivity, specificity, and areas under summary receiver-operating characteristic curve of magnetic resonance spectroscopy were calculated. Finally, seven studies with a total of 261 patients were included. Quantitative synthesis of studies showed that pooled sensitivity/specificity of Cho/NAA and Cho/Cr ratio in peritumoral region was 0.85 (95% confidence interval: 0.79–0.90)/0.93 (95% confidence interval: 0.80–0.99) and 0.86 (95% confidence interval: 0.76–0.92)/0.86 (95% confidence interval: 0.73–0.94). The area under the curve of the summary receiver-operating characteristic curve was 0.95 and 0.90. Pooled sensitivity, specificity, and area under the curve of magnetic resonance spectroscopy to identify high-grade gliomas from metastases were 0.85 (95% confidence interval: 0.79–0.90), 0.84 (95% confidence interval: 0.75–0.90), and 0.90, respectively. We concluded that magnetic resonance spectroscopy demonstrated moderate diagnostic performance in distinguishing high-grade gliomas from metastases. Furthermore, Cho/NAA ratio showed higher specificity and higher value of area under the curve than Cho/Cr ratio in peritumoral region. We suggest that Cho/NAA ratio of peritumoral region should be used to improve diagnostic accuracy of magnetic resonance spectroscopy for differentiating high-grade gliomas from metastases.